Attention, working-memory control, working-memory capacity, and sport performance: The moderating role of athletic expertise. Issue 2 (1st February 2021) - Vaughan, Robert S.; Laborde, Sylvain
ABSTRACT: The aim of this research was to detangle the association between attention, working-memory (focusing on both control and capacity functions), and sport performance across athletic expertise. Specifically, the mediating effect of working-memory-control and working-memory-capacity on the attention and performance relationship will be investigated, and whether this effect differs across athlete expertise. A sample of 359 athletes ( M age  = 18.91 ±  SD  = 1.01; 54.87% male) with a range of athletic expertise (novice n  = 99, amateur n  = 92, elite n  = 87, and super-elite n  = 81) completed a battery of neurocognitive tasks assessing attention, working-memory-control, working-memory-capacity, and a cognitively engaging motor task (e.g. basketball free-throw task). Athletes with more expertise performed better on tasks of attention, working-memory-control and working-memory-capacity. Results of structural equation modelling indicated a positive association between the cognitive measures and sport performance. Specifically, working-memory-control and working-memory-capacity mediated the attention and sport performance relationship. Additionally, invariance testing indicated larger effects for those with more athletic expertise. These findings provide a better understanding of how attention and the control and capacity functions of working-memory interact to predict performance. Theoretical and practical implications of these results are discussed.